Pola Kuman Dan Resistensi Bakteri Terhadap Antibiotik Pada Penderita Infeksi Saluran Kemih (ISK) Di Instalasi Rawat Inap Rumah Sakit PKU Muhammadiyah Surakarta Periode Februari Maret Tahun 2016 - Pradani, Sofia Adhitya, Prof. Dr. Kuswandi, SU., M.Phil., Apt, Maryati, Ph.D., Apt (2016)
Urinary tract infection (UTI) was a bacterial infection that occurs in the urinary tract. Management for the first-line therapy in patients with UTI was antibiotics. The problem of irrational use of antibiotics leads to resistance. Resistance to the use of antibiotics will result in the failure of therapy in patients with UTI. This study aims to determine patterns of bacteria and bacterial resistance to antibiotics in patients with urinary tract infections in inpatient hospital PKU Muhammadiyah Surakarta period from February to March 2016. This research was non-experimental descriptive. Samples were taken from the primary data that isolates the urine of patients urinary tract infection at the Hospital of PKU Muhammadiyah Surakarta period from February to March, 2016. Samples were identified by Gram staining and test its sensitivity to antibiotics using disk diffusion method on Mueller-Hinton agar medium. Data obtained inhibition zone diameter of antibiotic sensitivity test were analyzed according to the standard laboratory. Bacterial isolates from patients with UTIs be obtained 11 bacterial isolates showed that Gram-negative Escherichia coli (45.46%), Klebsiella pneumoniae (18.18%) while for Gram-positive as Staphylococcus aureus (36.36%). Escherichia coli was a bacterium that causes most UTIs and show resistance to the antibiotic amoxicillin, ampicillin, ceftriaxone and ceftazidime (100%), followed by cefepime, levofloxacin, chloramphenicol and trimetropim sulfamethoxazole respectively (60%), ciprofloxacin and cefepime respectively ( 40%), gentamicin (20%). Escherichia coli bacteria cause UTIs are still sensitive to the antibiotic amikacin and meropenem.